Employees' Perspectives on the Costs and Benefits of Organizations' Environmental Initiatives. Issue 4 (April 2023) - Allen, Stuart
Employee participation is essential to organizations' corporate social responsibility (CSR)-related environmental initiatives (EIs). Employees' attitudes to participating in pro-environmental behaviors are addressed in workplace literature drawing upon the theory of planned behavior. However, antecedents to employees' attitude formation, including perceptions of the costs and benefits of participating in EIs, have not been adequately researched. Greater understanding of EI attitude formation can support efforts to foster EI participation. This study explores employees' perceptions of EI costs and benefits to employees personally, to their organization, and to society by applying goal framing theory. A sample of 120 survey participants described 150 initiatives and identified personal, organizational, and societal costs and benefits of the EIs. Cost and benefit categories are presented along with a taxonomy and themes. The findings of this study provide a reference point for researchers and managers in understanding how employees view EIs and how employees might be encouraged to participate.